Effects of Herbicide, Glyphosate on Haematological Profile of Clarias batrachus (Linn.) - Paswan, Ranjan Kumar; Kumari, Arti (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The glyphosate (C3H8NO5P) is an herbicide widely used by farmers in agriculture to eradicate weeds. The present study includes the airbreathing fish, Clarias batrachus (Linn.) induced to sublethal concentration (2.46 mg/L) of inorganic herbicide, glyphosate for 30 days showed haematological profile alterations. In the treated group significant changes were observed in the haematological profile. The parameters Hb, RBC and WBC were decreases while in DLC, Neutrophil, Monocytes and Eosinophil an increases were observed. The present study concluded that Clarias batrachus is susceptible to herbicide, glyphosate at very low concentration. So, it is suggested that water contamination with glyphosate concentration of less than 2.46 mg/L in fish culture pond may be suitable for optimum growth performance.